2011
DOI: 10.1016/j.cortex.2009.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Unification of sentence processing via ear and eye: An fMRI study

Abstract: We present new evidence based on fMRI for the existence and neural architecture of an abstract supramodal language system that can integrate linguistic inputs arising from different modalities such that speech and print each activate a common code. Working with sentence material, our aim was to find out where the putative supramodal system is located and how it responds to comprehension challenges. To probe these questions we examined BOLD activity in experienced readers while they performed a semantic categor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
66
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(72 citation statements)
references
References 65 publications
5
66
1
Order By: Relevance
“…Numerous prior studies with fMRI have identified cortical regions that respond strongly (e.g., refs. 28, 37-41) and selectively (42)(43)(44) during sentence comprehension (whether presented visually or auditorily) (28,45), but fMRI lacks the temporal resolution to reveal the responses to individual words as a sentence is presented. Hence, little is known about how neural activity in specific cortical regions unfolds over the course of a sentence as the meaning of that sentence is extracted and represented.…”
Section: Significancementioning
confidence: 99%
“…Numerous prior studies with fMRI have identified cortical regions that respond strongly (e.g., refs. 28, 37-41) and selectively (42)(43)(44) during sentence comprehension (whether presented visually or auditorily) (28,45), but fMRI lacks the temporal resolution to reveal the responses to individual words as a sentence is presented. Hence, little is known about how neural activity in specific cortical regions unfolds over the course of a sentence as the meaning of that sentence is extracted and represented.…”
Section: Significancementioning
confidence: 99%
“…Semantic unification or the process by which small pieces of word-level information are combined into larger message-level representations ) is crucial to this goal. Neuroimaging studies using Positron Emission Tomography (PET) and functional Magnetic Resonance Imaging (fMRI) have revealed a number of brain regions involved in semantic unification, such as the left inferior frontal gyrus (LIFG) (Braze et al, 2011;Diaz et al, 2011;Hagoort et al, 2009;Huang et al, 2012;Rodd et al, 2005;Tesink et al, 2009;Zhu et al, 2009), anterior temporal lobe (ATL) (Crinion et al, 2003;Crinion and Price, 2005;Warren et al, 2009), posterior superior temporal gyrus (pSTG) (Friederici et al, 2009;Friederici et al, 2003) and angular gyrus (AG) (Friederici et al, 2003(Friederici et al, , 2009. Recent reviews Zhu et al, 2011) describe the LIFG as often being activated during semantic unification in fMRI studies.…”
Section: Introductionmentioning
confidence: 99%
“…S1) in at least 80% of subjects individually and to be robust to changes in stimulus modality (visual/auditory) (see also ref. 32), specific stimuli, and task (passive reading vs. reading with a probe task, which is used here). Furthermore, unlike the language contrasts used in some prior studies (17,21), this contrast does not confound linguistic processing and general cognitive effort, because the memory probe task is more difficult in the control (nonwords) condition.…”
mentioning
confidence: 99%